Notch regulates BMP responsiveness and lateral branching in vessel networks via SMAD6 - Kevin P. Mouillesseaux (Nature Portfolio, 2016)
The mechanism underlying endothelial cell responses to BMP signals is unknown. Here, the authors show that the endothelial response to pro-angiogenic BMP ligands is regulated by Notch via its effect on SMAD6, a known inhibitor of BMP intracellular signaling cascade.